PERBEDAAN EFEKTIFITAS PEMBERIAN ASI DAN SUSU FORMULA RENDAH LAKTOSA TERHADAP DURASI PENYEMBUHAN GASTRO ENTERITIS AKUT PADA ANAK USIA 2-12 BULAN - Santi, Dwi Erma (Jurnal Keperawatan Muhammadiyah, 2016)
Objective: to analyze the differences in the effectiveness of breastfeeding and low-lactose milk formula on healing duration Acute Gastro enteritis. Methods: These studies used cross sectional design with a sample of 34 pediatric patients were taken by systematic random sampling. The independent variables in this study were breastfeeding and low-lactose milk formula, while the dependent variable was the duration of the healing Acute Gastro enteritis. Results: Data obtained from observations of respondents and analyzed with statistical tests of T-2 free samples with significant levels of p <0.05. The result of the independent sample T-2 is P = 0.023 which means that there are differences in the effectiveness of breast-feeding and formula milk low-lactose towards healing duration Acute Gastro enteritis in children aged 2-12 months in space Siti Ismail Hospital Throughout Khodijah Conclusion: breastfeeding and formula feeding low-lactose equally consumed by the time the child diarrhea adapted to that consumed by children, when consuming breast milk alone before diarrhea, breastfeeding is still given for children with diarrhea with the recommendation had adopted a special diet to avoid diarrhea and can be combined with the provision of low-lactose formula, whereas when children consume milk formula, it is recommended immediately switching to low-lactose milk formula for children with diarrhea.